Implementasi Teknologi Informasi Pada Komunikasi Organisasi Kepengurusan Pondok Pesantren Al-Hidayah Ketegan Tanggulangin - Achmad Ali Yuddin Hakim; Wahyu Eko Pujianto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Information technology plays an important role in everyday life, including in communicating and facilitating work or daily activities, but the management organization of the al- hidayah boarding school has a slight difference in the implementation of the running of the organization, namely by not using a hand phone (hp) due to the permanent regulation of the al-hidayah Ketegan Tanggulagin boarding school that prohibits all students in the al hidayah Ketegan Tanggulangin boarding school from carrying hand phones (hp) and other electronic devices. The purpose of this research is to utilize information technology in terms of increasing communication effectiveness and overcoming the problem of communication failure in organizing and coordinating in each division. This research was conducted qualitatively and this research is descriptive, and is intended to explain organizational social events in detail. Information technology is a system or tool consisting of hardware and software that processes data systems quickly which aims to facilitate daily work or communication. communication is a reciprocal process of mutual understanding and understanding between individuals or both parties or more. As a result, communication in the boarding school management organization is more effective and failures in communication have been minimized both within the scope of all members or each division, by creating WhatsApp groups, using Hand talkies, making Youtube Chanels, payment applications and others.